(untitled) (San Francisco, CA, 2003)
Includes an overview of management theorists who have shaped modern thought about organizations and leadership, Contains complete, ready-made training exercises designed to meet a variety of needs for different audiences, Offers inventories that include questionnaires and instruments that help people clarify their own beliefs about leadership
Keywords: Leadership,Lãnh đạo; Problems, exercises, etc.,Câu hỏi, bài tập,...